Small-Scale Variability Dominates Benthic Coverage and Diversity Across the Jardines de La Reina, Cuba Coral Reef System - Hernández-Fernández, Leslie; González de Zayas, Roberto; Weber, Laura; Apprill, Amy; Armenteros, Maickel (Frontiers in Marine Science, 2019)
Coral reefs are complex and biodiverse ecosystems that are undergoing significant change. Understanding reef composition and biodiversity at multiple spatial scales is necessary to track both large-scale and more subtle ecosystem changes. The Jardines de la Reina (JR) archipelago, located offshore of the island of Cuba, contains the largest marine protected area (MPA) in the Caribbean Sea but lacks multi-scale studies. In this contribution, we documented the diversity of scleractinian corals, octocorals, algae, and sponges across nested spatial scales spanning four orders of magnitude (101–105 m). In addition, we tested the hypothesis that species diversity followed a gradient along the ca. 200 km of reef tract. Across the archipelago, we examined benthic cover and species diversity within 255 photo-quadrats (25 × 25 cm) at 13 fore reef sites (two sampling locations per site, and 10 photo-quadrats per location). Small-scale (101 m) variability between photo-quadrats characterized the coral reef community structure in JR compared with local- (102 m) and mesoscale (104–105 m) variability. This finding suggests that biological processes (e.g. recruitment, competition) had primacy over hydrodynamics for driving the differences in reef community composition. However, the dominance of algae and low cover and diversity of scleractinian corals suggests the pervasive effects of global change on coral communities despite potential benefits provided by the MPA (e.g. oligotrophy and abundance of herbivores). There was not a gradient of benthic community structure along the fore reef tract of JR; instead, a patchy distribution occurred in response to more subtle drivers acting at local scales. Overall, our multi-scale comparison was useful for differentiating the impacts of processes potentially impacting the JR reefs, thus providing important information to understand how reef communities are impacted by different environmental and anthropogenic stressors, and the potential benefits of MPAs.